Answer :

Firstly, equating x2 – x to 0 to find the zeros we get:

x (x – 1) = 0


x = 0 or x – 1 = 0


x = 0 or x = 1


As x3 + x2 – ax + b is divisible by x2 – x


The zeros o x2 – x will satisfy x3 + x2 – ax + b


Hence, (0)3 + 02 – a (0) + b = 0


b = 0


Also,


(1)3 + 12 – a (1) + 0 = 0


a = 2


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses